Frequency optimization and transient analyses of stiffened folded laminate composite plate using genetic algorithm - Van Binh, Bui; Ich Thinh, Tran; Minh Tu, Tran (Vietnam Journal of Science and Technology, 2017)
In this study, frequency optimization of stiffened folded laminate composite plate is investigated with respect to fiber orientations by using genetic algorithm (GA). The first order shear deformation theory was used for direct frequencies calculations. The Matlab programming using rectangular isoparametric plate element with five degrees of freedom per node was built to solve the problems. The modulus of selection, crossover and mutation were used as standard sub-modulus. The effects of obtained optimal fiber orientation on transient response of the folded plate have been investigated with difference boundary conditions. A good agreement was found between the results of this technique and other published results available in the literature.